2020
DOI: 10.1097/ta.0000000000002649
|View full text |Cite
|
Sign up to set email alerts
|

Combat medic testing of a novel monitoring capability for early detection of hemorrhage

Abstract: BACKGROUND Current out-of-hospital protocols to determine hemorrhagic shock in civilian trauma systems rely on standard vital signs with military guidelines relying on heart rate and strength of the radial pulse on palpation, all of which have proven to provide little forewarning for the need to implement early intervention prior to decompensation. We tested the hypothesis that addition of a real-time decision-assist machine-learning algorithm, the compensatory reserve measurement (CRM), used by co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Our results reveal that by using CRM over SBP and/or LAC, we were able to better predict those progressing to shock and requiring LSI. Although not temporally quantified in the current study, this earlier recognition has been shown to have significant translation in earlier identification of shock by civilian paramedics 29 and combat medics 30 …”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Our results reveal that by using CRM over SBP and/or LAC, we were able to better predict those progressing to shock and requiring LSI. Although not temporally quantified in the current study, this earlier recognition has been shown to have significant translation in earlier identification of shock by civilian paramedics 29 and combat medics 30 …”
Section: Discussionmentioning
confidence: 74%
“…Although not temporally quantified in the current study, this earlier recognition has been shown to have significant translation in earlier identification of shock by civilian paramedics 29 and combat medics. 30 Researchers have attempted to better predict or appreciate this "occult" shock through many devices such as tissue oxygen (StO 2 ) monitoring or lab analyses such as LAC and base deficit. Although these methods have shown promise, there remain questions in regards to their reliability and/or usefulness in the pre-hospital or forward-combat setting.…”
Section: Discussionmentioning
confidence: 99%
“…The high potential for delays in early and rapid medical evacuation in addition to mass casualty scenarios will require individualized triage decision to optimize medical resources and successfully execute prolonged field care. Integrating the CRM into prehospital medical monitoring on the battlefield could fill this capability gap by providing a medic with real‐time clinical status of injured casualties that will lead to earlier recognition for the need to intervene 33,34 . Such continuous monitoring of CRM could translate to optimizing combat casualty care of warfighters in austere, kinetic, and contested battlefield settings.…”
Section: Discussionmentioning
confidence: 99%
“…Integrating the CRM into prehospital medical monitoring on the battlefield could fill this capability gap by providing a medic with real-time clinical status of injured casualties that will lead to earlier recognition for the need to intervene. 33,34 Such continuous monitoring of CRM could translate to optimizing combat casualty care of warfighters in austere, kinetic, and contested battlefield settings.…”
Section: Discussionmentioning
confidence: 99%
“…This dynamic analysis applies a scale from 0% to 100% where 100% represents a complete capacity to compensate (e.g., a “full” fuel tank) and 0% represents the point where decompensated shock occurs. A potential for a color‐coded dashboard can provide for more rapid detection of where the patient lies along this cascade 17–20 . “Green” represents a reserve range of 100%–60%, “yellow” represents a reserve range of 60%–30%, and “red” represents a reserve range of 30%–0% reflecting the continuum toward decompensation.…”
Section: Introductionmentioning
confidence: 99%